Tissue-specific extracellular matrix scaffolds for the regeneration of spatially complex musculoskeletal tissues - Kelly, Daniel; Dunne, Aisling; Cunniffe, Gráinne M.; Díaz-Payno, Pedro J.; Sheehy, Eamon J.; Critchley, Susan E.; Almeida, Henrique V.; Pitacco, Pierluca; Carroll, Simon F.; Mahon, Olwyn R.; Levingstone, Tanya J.; Moran, Conor J.; et al. (My University, 2019)
Biological scaffolds generated from tissue-derived extracellular matrix (ECM) are commonly used clinically for soft tissue regeneration. Such biomaterials can enhance tissue-specific differentiation of adult stem cells, suggesting that structuring different ECMs into multi-layered scaffolds can form the basis of new strategies for regenerating damaged interfacial tissues such as the osteochondral unit. In this study, mass spectrometry is used to demonstrate that growth plate (GP) and articular cartilage (AC) ECMs contain a unique array of regulatory proteins that may be particularly suited to bone and cartilage repair respectively. Applying a novel iterative freeze-drying method, porous bi-phasic scaffolds composed of GP ECM overlaid by AC ECM are fabricated, which are capable of spatially directing stem cell differentiation in vitro, promoting the development of graded tissues transitioning from calcified cartilage to hyaline-like cartilage. Evaluating repair 12-months post-implantation into critically-sized caprine osteochondral defects reveals that these scaffolds promote regeneration in a manner distinct to commercial control-scaffolds. The GP layer supports endochondral bone formation, while the AC layer stimulates the formation of an overlying layer of hyaline cartilage with a collagen fiber architecture better recapitulating the native tissue. These findings support the use of a bi-layered, tissue-specific ECM derived scaffolds for regenerating spatially complex musculoskeletal tissues.
PUBLISHED
Keywords: Extracellular matrix; Scaffold; Growth plate; Articular cartilage; Osteochondral defect